Serum amyloid P inhibits dermal wound healing - Naik-Mathuria, Bindi (2008)
The repair of open wounds depends on granulation tissue formation and contraction, which is primarily mediated by myofibroblasts. A subset of myofibroblasts originates from bone-marrow-derived monocytes which differentiate into fibroblast-like cells called fibrocytes. Serum amyloid P (SAP) inhibits differentiation of monocytes into fibrocytes. Thus, we hypothesized that the addition of exogenous SAP would hinder the normal wound healing process. Excisional murine dorsal wounds were either injected with SAP (intradermal group) or the mice were treated with systemic SAP (intraperitoneal group) and compared with animals treated with vehicle. Grossly, SAP-treated wounds closed slower than respective controls in both groups. Histologically, the contraction rate was slower in SAP-treated wounds in both groups and the reepithelialization rate was slower in the intraperitoneal group. Furthermore, significantly less myofibroblasts expressing α-smooth muscle actin were noted in the intraperitoneal group wounds compared with controls. These data suggest that SAP delays normal murine dermal wound healing, probably due to increased inhibition of fibrocyte differentiation, and ultimately a decreased wound myofibroblast population. SAP may provide a potential therapeutic target to prevent or limit excessive fibrosis associated with keloid or hypertrophic scar formation. Furthermore, SAP removal from wound fluid could potentially accelerate the healing of chronic, nonhealing wounds.